1989
DOI: 10.1007/bf00024771
|View full text |Cite
|
Sign up to set email alerts
|

A possible regulatory role for ethylene in the pollen-pistil interaction in a sporophytic self-incompatible system

Abstract: The sporophytic type of self-incompatibility exhibited by Ipomoea cairica Sweet (Convolvulaceae) was partially overcome in vitro by treating the pollen and/or stigma with 10 -'to 10 -'M methionine, a precursor of ethylene . The implications of these observations are discussed in relation to other experiments involving use of the ethylene antagonist AgNO 3 , individually and in combination with methionine and an optimum level of indole-3-acetic acid (10 -'M). The results suggest a role for ethylene (which could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The auxin content of the style increased substantially after pollination [16,17], implying its de novo synthesis . These studies as well as our previous observations [7,24] have indicated a role for auxin in pollination and interaction of the two partners thereafter . The IAA-forming enzymes have been shown to increase following GA3 treatment [13,151 .…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…The auxin content of the style increased substantially after pollination [16,17], implying its de novo synthesis . These studies as well as our previous observations [7,24] have indicated a role for auxin in pollination and interaction of the two partners thereafter . The IAA-forming enzymes have been shown to increase following GA3 treatment [13,151 .…”
Section: Introductionmentioning
confidence: 62%
“…Most experimentation was done with Ipomoea cairica Sweet, due to the advantages it has over other taxa [7] . However, in order to obtain relevant information, some growth regulators known to partially remove the barrier to self-compatibility were also employed on two other taxa belonging to the Brassicaceae .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations